2001
DOI: 10.1046/j.1365-2125.2001.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unexpected death in infants under 3 months of age and vaccination status – a case‐control study

Abstract: Aims To determine whether DTPP+Hib vaccination (diphtheria, tetanus, pertussis, poliomyelitis +/x haemophilus) increased the risk of sudden unexpected death (SUD) in children under 3 months of age. Methods We conducted a multicentre case-control study in the 28 French`SIDS Centers'. Case selection was based on death labelled sudden infant death syndrome (SIDS) of an infant aged between 30 and 90 days. Three living controls were selected, matched for sex, gestational age and born immediately after the victim in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 20 publications
1
18
0
3
Order By: Relevance
“…[312][313][314][315] Casecontrol studies were performed to evaluate this temporal association. Four of the 6 studies found no relationship between diphtheria-tetanuspertussis vaccination and subsequent SIDS, [316][317][318][319] and results of the other 2 studies suggested a temporal relationship but only in specific subgroup anal- [323][324][325] ; however, confounding factors (social, maternal, birth, and infant medical history) might account for this protective effect. 326 It also has been theorized that the decreased SIDS rate immediately after vaccination was attributable to infants being healthier at time of immunization, or "the healthy vaccinee effect."…”
Section: Infants Should Be Immunized In Accordance With Recommendatiomentioning
confidence: 99%
“…[312][313][314][315] Casecontrol studies were performed to evaluate this temporal association. Four of the 6 studies found no relationship between diphtheria-tetanuspertussis vaccination and subsequent SIDS, [316][317][318][319] and results of the other 2 studies suggested a temporal relationship but only in specific subgroup anal- [323][324][325] ; however, confounding factors (social, maternal, birth, and infant medical history) might account for this protective effect. 326 It also has been theorized that the decreased SIDS rate immediately after vaccination was attributable to infants being healthier at time of immunization, or "the healthy vaccinee effect."…”
Section: Infants Should Be Immunized In Accordance With Recommendatiomentioning
confidence: 99%
“…In our review, 19 of 24 studies satisfied all 6 criteria; the failed criteria of 5 studies are listed in Table 1. 2,9,16,19,32 Another study could not be included because the ORs were presented in a way that was not compatible with our analyses, 33 which resulted in a total of 18 studies for the meta-analysis.…”
Section: Data Extractionmentioning
confidence: 99%
“…Two reviewers (Dr Hauck and Ms Tanabe) reviewed all pulled articles for inclusion and for overlapping data. Twenty-four original case-control studies that provided data on the relationship between breastfeeding and SIDS risk 2,[5][6][7][8][9][10][11][14][15][16][17][18][19][24][25][26][27][28][29][30][31][32][33] were identified. Two teams of 2 reviewers independently evaluated 12 studies each according to preset criteria; in cases of disagreement, a third reviewer evaluated the study, and a consensus opinion was reached.…”
Section: Data Sources and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Indeed, recent evidence suggests that immunization might have a protective effect against SIDS. [81][82][83] Infants should also be seen for regular well-child checks in accordance with AAP recommendations. 12.…”
Section: Introductionmentioning
confidence: 99%